(untitled) (Damascus University Journal for engineering sciences, 2025)
Due to the huge rise in the prices of petroleum products in the current period, the purchase of crude oil in foreign exchange, and the outage of many oil wells due to the clear and systematic sabotage of oil facilities, this led to the thinking of using and treating this Al-Beshery Natural Asphalt produced from natural quarries after improving its physical and chemical properties to achieve the standard specifications required for paving roads, and this represents an important national goal for paving roads at a low capital cost while ensuring the quality of construction and achieving the targeted life span, Natural asphalt is a material that can be produced and consumed again, It is a tributary to the national economy at a small capital cost, note that the Asphalt refineries used to supply us previously, before the crisis, with 20-30% of the road network needs in our country.This research aims in its early stages to determine the chemical and physical properties of the available produced materials from Natural asphalt in various grades and types in which these materials are used and a study of the extent to which these characteristics achieve the international standard specifications, Then the research aims to study the best scientific, economic and practical methods available to improve the physical and chemical properties of those aged asphalt binders, And to know scientifically and accurately the optimal proportions of rejuvenating materials from refinery asphalt and other treated materials added to the asphalt binder existing in Natural asphalt in order to use it in road paving again.The results of chemical and physical properties indicate that Natural asphalt lacks the required properties to ensure the achievement of its design life as a result of its exposure to oxidation and polymerization factors in the summer and winter seasons during its existence in nature for millions of years, The research has proven the possibility of improving these properties by using economical and practical additives, which are relatively soft asphalt, it has a penetration of +300 and is considered fuel, with a practical ratio ranging between (30-45%) approximately of the weight of the asphalt material in the mixture, or the usual lubricating used oil with a percentage of approximately 8%, it also includes the detailed results of the various tests that were conducted on the asphalt binder used in paving mixes using these improvers. Finally, this research includes the conclusion and recommendations reached in this research, whether from the scientific or practical aspects